Item Analysis of Final Test for the 9th Grade Students of SMPN 44 Surabaya in the Academic Year of 2019/2020 - Siti Fatimah; Achmad Bernhardo Elzamzami; Joko Slamet (STKIP PGRI SIDOARJO, 2020)
This research was conducted by focusing on the formulated question regarding the test scores validity, reliability and item analysis involving the discrimination power and index difficulty in order to provide detail information leading to the improvement of test items construction. The quality of each particular item was analyzed in terms of item difficulty, item discrimination and distractor analysis. The statistical tests were used to compute the reliability of the test by applying The Kuder-Richardson Formula (KR20). The analysis of 50 test items was computed using Microsoft Office Excel. A descriptive method was applied to describe and examined the data. The research findings showed the test fulfilled the criteria of having content validity which was categorized as a low validity. Meanwhile, the reliability value of the test scores was 0.521010831 (0.52) categorized as lower reliability and revision of test. Through the 50 items examined, there were 21 items that were in need of improvement which were classified into “easy” for the index difficulty and “poor” category for the discriminability by the total 26 items (52%). It means more than 50% of the test items need to be revised as the items do not meet the criteria. It is suggested that in order to measure students’ performance effectively, essential improvement need to be evaluated where items with “poor” discrimination index should be reviewed.